Pengelolaan Wakaf Uang oleh Nazhir untuk Kesejahteraan Umat (Studi kasus di Dompet Amal Sejahtera Ibnu Abbas Nusa Tenggara Barat) - Muliani Muliani; Muhammad Irwan; Moh. Huzaini (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2019)
This study analyzes the management of waqf money by Nazhir for the welfare of the people (case study in Ibn Abbas West Nusa Tenggara's Amal Amal Sejahtera Wallet) using qualitative research methods, to understand the phenomena experienced by the research subjects in behavior, perception, motivation, actions and others. others then describe the state of the object of the researcher about the correspondence between theory and reality (empirical) that occurs. The results showed that the management of waqf was carried out in accordance with management management in Islam and in accordance with George R.Terry's theory of management management theory and function. Money Waqf has been able to provide prosperity for the people through programs launched by DASI NTB which are engaged in the social field to help the community to compensate for the necessities of daily life which is the goal of the management function in Islam. The Deputy Secretary has understood money waqf because according to informants waqf money is a charity Jariyah intended for his family who has died, in accordance with the hadith of the Messenger of Allah on the hand of alms.